Surgical Challenges in the Management of Liver Disease - Tsoulfas, Georgios (IntechOpen, 2019)
Hepatic surgery represents one of the most challenging fields of surgical practice because it combines the need for surgical excellence with that for deep knowledge and understanding of liver physiology. The various hepatic diseases, whether they are benign or malignant, require surgical expertise in their management, especially given the complex anatomy and physiology of the liver, as well as its critical role in a variety of different biologic functions.This book is a collection of chapters offering the reader distilled knowledge of various worldwide experts in hepatic surgery and hepatic physiology. The surgical management, including complex and demanding surgical procedures, of malignancies such as hepatocellular carcinoma, cholangiocarcinoma, and metastatic disease will be addressed in an effort to present the various therapeutic choices in the surgical armamentarium.Emphasis is given to the molecular aspect of the different mechanisms involved, which offers a glimpse into the future, given the ever-increasing need for precision medicine and surgery, leading to a patient-targeted approach.